Comparison Of Meaningful Sound vs No Sound For Avoiding Attention Drifting Phenomenon While Driving - Shafiee, Super; Mai Mariam, Mohamed Aminuddin; Hairulisam, Md Dom (Penerbit Universiti, UTeM, 2016)
One of the causes of traffic accident is attention drifting while driving. Attention drifting is also known as habituation phenomenon. Habituation phenomenon refers to a situation where one’s attention would decay and possibly diminish over time due to repetitive stimuli. Hence, the aim of this study is to investigate the types of sound that can avoid attention drifting while driving. Using a driving simulation system, the subjects will be simulated with two conditions while driving: no sound and recorded speech. It was found that drivers encounter less accident while listening to the recorded speech compared to the silent condition (no sound). This finding could be used as a foundation to develop tips or methodology to avoid the attention deficit while driving.